Analysis of urinary fatty acids in bovine (Bos taurus): An effective method for estrus detection - Kumar, K Ramesh; Archunan, G (The Indian Journal of Animal Sciences, 2011)
The present study was carried out to detect fatty acid profiles in bovine urine to establish the qualitative and quantitative differences that might have potential value in detection of estrus. The urine from the bovine of different reproductive phases (estrous cycle, pregnant, lactating and prepubertal) was analyzed using gas-chromatography (GC). Fatty acids tridecanoic, myristic and pentadecanoic acids and the lipids of the bovine urine were comparatively higher during estrus compared to all other stages. It indicates that the appearance ofthese specific fatty acids and lipids are because of the high circulation ofsteroidal hormones, and may be involved in opposite sex attraction. The present result is consistent with the view of increased amount of these fatty acids of bovine urine involved in odour production and may act as pheromones. However, in the lactating female's urine, the fatty acids such as stearic, heptadecanoic and nondecanoic acids were present in higher quantity than all other stages. These fatty acids present in the lactating dam's urine may be involved in mother-young interactions. Thus, the presence ofspecific fatty acids and lipid content in estrus urine make the possibility to develop a biomarker for the detection of estrus.